Motility study in right sided diverticular disease of the colon. Issue 12 (December 1983) - Sugihara, K; Muto, T; Morioka, Y
Abstract : Intraluminal pressure in the ascending colon of 13 patients with right sided diverticular disease and 10 of normal subjects was studied with catheter-tip transducer inserted through colonoscopes. In the resting state the colonic motility index of patients with diverticular disease was greater than that of the controls. After intravenous injection of neostigmine methylsulphate higher pressure waves were more frequently observed in patients with diverticular disease than the controls, and the colonic motility index of patients was much greater than that of the controls with statistical significance. From these observations it is suggested that high intraluminal pressure and the abnormal motility in the ascending colon plays an important role in the pathogenesis of right sided diverticular disease.